RBIO-03. A MULTI-INSTITUTIONAL EXPERIENCE OF GAMMATILE BRACHYTHERAPY AS TREATMENT FOR RECURRENT GLIOBLASTOMAS. (14th November 2022) - Chen, Clark; Ferreira, Clara; Dusenbery, Kathryn; Hoang, Kimberly; Lee, Stuart; Smith, Kris
Abstract: BACKGROUND: Recurrent glioblastoma remains a disease without established standard of care. Here, we report the safety profile and survival outcome of recurrent glioblastoma patients treated with maximal safe resection followed by intraoperative placement of GammaTile (GT), a collagen tile-embedded Cs-131 brachytherapy platform. METHODS: The study included isocitrate Dehydrogenase (IDH) wild-type glioblastoma patients who suffered tissue confirmed recurrence after concurrent temozolomide-radiation therapy. The series included consecutively patients treated at the University of Minnesota, Barrow Neurological Institute, Vidant Health, and Emory University Hospital. Survival results were stratified by methyl-guanine methyl transferase (MGMT) promoter methylation status RESULTS: In total 48 patients were treated between 2019 and 2022 in this multi-institutional experience. The median days of hospitalization following the procedure was two (range: 1-15), with 72.5% of the GT implanted patients discharged home before postoperative day three. In terms of post-operative course, two patients suffered new-onset seizure post-surgery (4.0%). There was one (2%) 30-day mortality from intracranial hemorrhage secondary to heparinization for an ischemic limb. There were 13% readmission within 30 days, including hydrocephalus (n=2), urinary tract infection (n=1), deep venous thrombosis (n=1), failure to thrive (n=1), and infected wound (n=1). Of note, the patient with the infected wound had suffered a previous wound infection prior to the GT implantation and the pathogenic organism for both infections were the same (S. aureus). With a median follow-up of 250 days, twelve-month local control was 82%. Median overall survival (OS) from the time of diagnosis was 19 and 33 months for the MGMT unmethylated and methylated tumors, respectively. Select patients (n = 6) treated with adjuvant ketogenic diet in addition to GT and subsequent chemotherapy exhibited survival beyond expectation (> 14 mo, median survival not reached). CONCLUSION: This multi-institutional experience supports further investigation of GT brachytherapy as a treatment for recurrent glioblastomas.